Song overlapping, noise, and territorial aggression in great tits. (29th March 2020) - Akçay, Çağlar; Porsuk, Y Kağan; Avşar, Alican; Çabuk, Dilan; Bilgin, C Can
Abstract: Communication often happens in noisy environments where interference from the ambient noise and other signalers may reduce the effectiveness of signals which may lead to more conflict between interacting individuals. Signalers may also evolve behaviors to interfere with signals of opponents, for example, by temporally overlapping them with their own, such as the song overlapping behavior that is seen in some songbirds during aggressive interactions. Song overlapping has been proposed to be a signal of aggressive intent, but few studies directly examined the association between song overlapping and aggressive behaviors of the sender. In the present paper, we examined whether song overlapping and ambient noise are associated positively with aggressive behaviors. We carried out simulated territorial intrusions in a population of great tits ( Parus major ) living in an urban–rural gradient to assess signaling and aggressive behaviors. Song overlapping was associated negatively with aggressive behaviors males displayed against a simulated intruder. This result is inconsistent with the hypothesis that song overlapping is an aggressive signal in this species. Ambient noise levels were associated positively with aggressive behaviors but did not correlate with song rate, song duration, or song overlapping. Great tits in noisy urban habitats may display higher levels of aggressive behaviors due to either interference of noise in aggressive communication or another indirect effect of noise. Abstract : Overlapping a rival's song with one's own is associated with lower aggression, while ambient noise is associated with higher aggression in male great tits. Male great tits holding territories in areas that vary from noisy urban habitats to quieter forest habitats respond differently to intruders depending on the ambient noise levels. However, they do not appear to signal their aggressive intent by starting to sing while their opponent is still singing.